Development of The Media Game Math City Based on Character Education to Improve Critical Thinking Ability - Putry Regita Sari, Ayu; Sulistyaningsih, Dwi; Joko Suprayitno, Iswahyudi (Education, Science, and Technology International Conference, 2024)
The low critical thinking ability of students is caused by a lack of skills in understanding and identifying problems, applying appropriate problem-solving strategies, and drawing conclusions from the solutions. The aim of this research is to develop a character education-based learning media game, Math City, to enhance valid, practical, and effective critical thinking skills, showing improvement. The research methodology employed the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development method. Data collection techniques included observation, questionnaires, and critical thinking ability tests. Sampling was conducted using simple random sampling. The development of the Math City game media received validation scores from media and subject matter experts of 3.80, falling within the valid category, and student and teacher responses averaged 3.26, indicating it is practical. The experimental group's average N-Gain score was 0.45, which is moderate, while the control group's average was 0.17, considered low. The implementation of the Math City game media achieved critical thinking mastery, with classical completeness proving scores above the target score of 71, specifically 81.82, with 85% classically at 94.117%, with 32 out of 34 students achieving mastery. There was a 20.4% influence from learning motivation, and a difference in average critical thinking ability scores between the experimental class at 81.82 and the control class at 70.26. The recommendation from this research is for teachers to optimally use the Math City game media in teaching to engage students effectively.